Data Development Trend of Public/Private Medical Institutions in Chinese Plastic and Aesthetic Major - ZHANG Mingzi; SI Loubin; ZHENG Jiaojie; CHEN Jie; WANG Xiaojun; LONG Xiao; XIONG Wei (Xiehe Yixue Zazhi)
ObjectiveTo compare and understand the trends in quality control data changes in public and private medical institutions specializing in plastic and aesthetic major in China over the past three years.MethodsThe national quality control center of plastic and aesthetic major formulated quality control indicators, collected indicator data through the National Clinical Improvement System, conducted feedback verification on the data, organized and summarized the final data, and convened expert committees to analyze the data change trends.ResultsIn the past three years, the number of both public and private medical institutions specializing in plastic and aesthetic major has shown an upward trend. The number of doctors increased significantly in 2022, with over 90% of doctors in public institutions (about 70% in private institutions) receiving higher education. In recent years, the proportion of doctors from other specialties engaging in plastic and aesthetic activities has increased. The proportion of inpatients seeking aesthetic treatments has also increased. Among outpatient patients, the proportion of injection procedures was relatively low. About one-third of private medical institutions have not yet adopted an electronic medical record system.ConclusionsData feedback is the cornerstone of medical quality control in Chinese plastic and aesthetic major. Existing data indicates that the related industry is developing steadily, but there is still room for improvement in terms of some indicator data. However, due to the limited data from private medical institutions, it is still necessary to encourage them to improve their reporting enthusiasm in order to conduct a more comprehensive assessment in the future.